2017
DOI: 10.1007/s12094-017-1629-y
|View full text |Cite
|
Sign up to set email alerts
|

Selection of DNA aptamers for extra cellular domain of human epidermal growth factor receptor 2 to detect HER2 positive carcinomas

Abstract: Binding assays, cytochemical and histochemical studies support ECD_Apt1 as a potential theranostic agent for Her2-positive carcinomas. ECD_Apt1 could be an effective low-cost alternative to conventional anti-Her2 antibody in solid phase immunoassays for cancer diagnosis and related applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…As shown in Figure 3A, after the fixed SKBR-3 cells were treated with Apt2-G4 probes and implemented intact DCTDR system, cells showed bright and clear green fluorescence, indicating the Apt2-G4 probes can bind with the HER2 proteins on the cell surface and triggered DCTDR in situ for HER2 protein imaging. The fluorescence signals distributed mainly on the cell surface but partly in cytoplasmic surroundings of SKBR-3 cells, which is in accordance with the imaging results of the original article for this aptamer development, due to enhanced cell penetration ability of DNA aptamer 23. Meanwhile, there was no detectable fluorescence image, when Apt2-G4 or hemin was absent in the DCTDR system.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…As shown in Figure 3A, after the fixed SKBR-3 cells were treated with Apt2-G4 probes and implemented intact DCTDR system, cells showed bright and clear green fluorescence, indicating the Apt2-G4 probes can bind with the HER2 proteins on the cell surface and triggered DCTDR in situ for HER2 protein imaging. The fluorescence signals distributed mainly on the cell surface but partly in cytoplasmic surroundings of SKBR-3 cells, which is in accordance with the imaging results of the original article for this aptamer development, due to enhanced cell penetration ability of DNA aptamer 23. Meanwhile, there was no detectable fluorescence image, when Apt2-G4 or hemin was absent in the DCTDR system.…”
Section: Resultssupporting
confidence: 85%
“…HER2 protein was chosen as the model. HER2 specific aptamer (Apt2) 23 and intact G-quadruplex sequence (G4) were incorporated to design a bifunctional Apt2-G4 probes for total HER2 protein analysis. The recognition of HER2 protein with the aptamer part can present the hemin/G4 DNAzyme on the cell surface and subsequently initiated DCTDR in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, several aptamers were also developed to target human epidermal growth factor 2. These were used to deliver therapeutic drugs, RNA, and nanoparticles into the cancer cells [ 76 , 77 ].…”
Section: Aptamers As Therapeutic Agentsmentioning
confidence: 99%
“…This RNA aptamer could bind with HER2 positive cell line MDA-MB-453 and KPL-4 but had no affinity towards HER2 negative cells such as MCF-7 and A431. In another study, Sett et al reported the isolation of DNA aptamer ECD_Apt1 to specifically target extracellular domain of HER2 protein [ 67 ] and then conjugated the ECD_Apt1 aptamer with biotin. This biotin-aptamer conjugate showed stronger cytoplasmic staining in SKBR3 compared to MDA-MB-231 and MCF-7.…”
Section: Applications Of Aptamer In Breast Cancermentioning
confidence: 99%